Construction and Identification of New Molecular Markers of Triple-Negative Breast Cancer Stem Cells - Liu, Tingting; Wang, Hongyue; Liu, Zhiyong; Zhang, Jing; Liu, Yan; Zhang, Lin; Zheng, Chunhui; Liu, Fei; Hou, Chuanqiang; Li, Baojiang (Frontiers in Oncology, 2021)
Abstract: Breast carcinoma is the most common malignancy and major cause of cancer death in women worldwide, and triple-negative breast cancer (TNBC) accounts for approximately 15% to 20% of all cases. TNBC is characterized by the absense of estrogen, progesterone, and human epidermal growth factor 2 receptors. TNBC patients usually have shorter disease-free survival and overall survival compared with non-TNBC breast cancer cases. Until now we still lack specific molecular marker of TNBC, therefore, we aimed to screen new molecular markers of TNBC stem cells and identify the specificity in virto and in vivo furtherly. Objective: We screened the TNBC stem cells using phage display, acquired the specific binding clones and then we sent them to amplify and extract the positive phage DNAs, synthesized specific polypeptides and labeled with FITC. Finally, we identified the specificity of the polypeptides in vitro and in vivo. Methods: Human breast cancer cell line MDA-MB-231 and human mammary gland cell line hs578st were chosen in our study, MDA-MB-231 breast cancer stem cells(BCSCs) were cultured and identified by flow cytometry. The phage peptide library was screened using MDA-MB-231 BCSCs, the positive phage clones were identified by ELISA and the DNA of positive phage were extracted, the they were send to biotechnology company for sequencing. According to the sequencing results, a specific polypeptide was synthesized and labeled with FITC. In the end, the specificity of polypeptide to BCSCs was identified respectively in vivo and in vitro. Results: The MDA-MB-231 BCSCs were cultured and enriched with the “serum and serum-free alternate” method. The breast cancer stem cells were found to have characteristic of CD44+/CD24-/low ESA and ALDH+ with flow cytometry. The phage was enriched to 200-fold after three rounds of screening for MDA-MB-231 BCSCs. The positive phages were sequenced, then polypeptide named A1 was synthesized according to sequencing results. The polypeptide A1 has specific affinity to MDA-MB-231 BCSCs in vivo and in vitro. Conclusion: Specific polypeptides binding to MDA-MB-231 breast cancer stem cells were screened out by phage display screening method, which laid a theoretical foundation for the targeted therapy and further research of breast cancer stem cells.